types and abundance of periphyton attached in the lotus leaves at the Bandar Kayangan Reservoir Pekanbaru, Riau Province - Framindo G. Napitupulu; Nur El Fajri; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPeriphyton is a sessile microscopic organism that attach on certain substrate. A research aims to understand types and abundance of periphyton attached in the lotus leaves present in the Bandar Kayangan dam, Pekanbaru has been conducted Februari 2019. There were 3 stations, around floating caged fish culture (Station 1), in the water closed to teak plantations (Station 2) and in the recreational area (Station 3). Samplings were conducted 3 times, once/week. Lotus leaves were collected and periphytons were obtained through scraping upper and lower surface of the leaf (5 ×5 cm). Periphyton collected were preserved using Lugol 1% and then were indentified. Result shown that there were 24 periphyton species present and they were belonged to classes, Cynanophyceae (3 species), Chlorophyceae (5 species), Bacillariophycea (11 species), and Euglenophyceae (1 species). Abundance of the periphyton ranged from 2,317-2,621 cells/cm2, diversity index was 4.148-4.242 and dominancy index was 0.054-0.060. Based on data obtained, it can be concluded that the Bandar Kayangan dam water was fertile..Keywords:lotic, sessile organism, natural substrats, trophic state